2019
DOI: 10.3390/en12183415
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Thermal Insulation Thicknesses of External Walls Based on Economic and Ecological Heating Cost

Abstract: The present study introduces the concept of ecological cost of heating modeled on the economic cost of heating. A method of determining these costs is also proposed. This method allows for an analytical description of the ecological as well as economic net present value of a thermal insulation investment. Consequently, it is possible to determine the optimal values for ecological reasons of the heat transfer coefficient of the building external wall and the thickness of thermal insulation. The present study us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 11 publications
2
14
0
Order By: Relevance
“…The temperature of the outer surface of the outer wall was determined from the balance sheet ( Figure 8): Taking into account the Equations (10)- (12) and the heat conduction equation under the surface of the partition (24), it can be concluded that:…”
Section: Heat Losses Through the External Wall-case Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The temperature of the outer surface of the outer wall was determined from the balance sheet ( Figure 8): Taking into account the Equations (10)- (12) and the heat conduction equation under the surface of the partition (24), it can be concluded that:…”
Section: Heat Losses Through the External Wall-case Studymentioning
confidence: 99%
“…In the work [23], it has been shown that the convective heat transfer coefficient value strongly depends on the wind velocity. The influence of the thermal insulation thicknesses of external walls on heating cost from the ecological and economic assessment is analyzed in [24].…”
Section: Introductionmentioning
confidence: 99%
“…However, the main target group of materials are innovative materials for further development rather than mass-produced insulation. The eco-friendly thermal insulation materials are much more expensive in comparison to the traditional thermal insulation materials almost in all cases [26] and the price is less crucial than the environmental effect. This study focuses on the fibers from the hemp used for soil regeneration before it ripens.…”
Section: Introductionmentioning
confidence: 99%
“…Dylewski [17] studied the environmental impact of diverse thermal insulation materials for exterior walls in Poland, considering alternative heat sources, in order to find the optimal insulation thickness considering both economic and ecological net present value of insulation (as an investment). Results showed that significantly higher thicknesses were recommended when considering environmental data as compared to economic data-for instance, 0.46-0.52 m of expanded polystyrene (EPS) insulation considering brick walls and a heat pump system.…”
Section: Introductionmentioning
confidence: 99%